Throughput of slotted ALOHA in Nakagami fading and correlated shadowing environment - Abdel-Hafez, M; Safak, M (Iee-Inst Elec Eng, 1997)
The throughput of a slotted ALOHA radio channel is evaluated in a Nakagami fading and correlated shadowing environment. General and closed form expressions are derived for the throughout. The effects of fading parameters of both the desired and interfering packets, shadow spread, and correlation coefficient are considered.
Keywords: fading; mobile radio systems; channel capacity